Factors associated with the performance of self-care activities in diabetic patients in three Ucayali hospitals - Jennifer Vilchez-Cornejo; Luccio Romani; Silvia Reategui; Elice Gomez-Rojas; Claudia Silva (Revista de la Facultad de Medicina Humana, 2020)
OBJECTIVES: To determine the levels and assessment of self-care in diabetic patients in three hospitals in Ucayali during 2017. MATERIALS AND METHODS: Analytical cross-sectional study, conducted in three hospitals in Ucayali during 2017 with a sample size of 572 participants through a stratified random sampling. A self-administered survey was applied that evaluated the general characteristics, the Diabetes Knowledge Questionnaire 24 (DQK-24), the patient's attitude by the Diabetes Attitude Scale (DAS-3) and Summary of Diabetes Self Care Activities Measure (SDSCA) which mediates self-care practices. RESULTS: From 572 patients, 50.8% being women, with the median age of 47 years (RIQ: 35-56). Hypertension (22.4%) was the most frequent comorbidity. Also, having an adequate knowledge about their disease (RPa: 2.47; 95% CI: 13.5-4.50), strict control (RPa: 1.34; 95% CI: 1.09-1.65) predispose adherence in their diet. The need for some special training (RPa: 1.23; 95% CI: 1.03-1.47), the perception of the severity in their illness (RPa: 1.25; 95% CI: 1.02-1.55) and have autonomy (RPa: 1.35; 95% CI : 1.12-1.64) predisposed to taste your blood sugar. CONCLUSIONS: More than half of the patients performed inadequate self-care activities, knowledge about their disease and strict control influence the patient's diet, as well as special training, perceive the severity of their disease and be autonomous drives the realization of taste blood sugar.